The Consent Paradox: Accounting for the Prominent Role of Consent in Data Protection - Benjamin Bergemann (Privacy and Identity Management. The Smart Revolution, 2018)
The concept of consent is a central pillar of data protection. It features prominently in research, regulation, and public debates on the subject, in spite of the wide-ranging criticisms that have been levelled against it. In this paper, I refer to this as the consent paradox. I argue that consent continues to play a central role not despite but because the criticisms of it. I analyze the debate on consent in the scholarly literature in general, and among German data protection professionals in particular, showing that it is a focus on the informed individual that keeps the concept of consent in place. Critiques of consent based on the notion of “informedness” reinforce the centrality of consent rather than calling it into question. They allude to a market view that foregrounds individual choice. Yet, the idea of a data market obscures more fundamental objections to consent, namely the individual's dependency on data controllers' services that renders the assumption of free choice a fiction.
Additional information: Akzeptierte Manuskriptfassung (postprint) / Accepted version (postprint)
Keywords: 330; commodification; data protection; discourse analysis; informed consent; information control; power